2016
DOI: 10.12659/msm.896331
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Pelvic Floor Disorders: A Review of the Literature

Abstract: Overweight and obesity are becoming a worldwide health problem associated with numerous co-morbidities. National costs of obesity and pelvic flor disorders have been rising since the 1950s across the world. Obesity is thought to have a very strong effect on pelvic floor disorders, and, considering the high prevalence of both problems worldwide, it is of utmost importance to evaluate the association between these pathologies as well as the impact of obesity on treatment efficacy. This review is based on a selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 68 publications
2
46
1
5
Order By: Relevance
“…In this previous study, frailty was measured by TUGT and a slow TUGT exhibited a significant association with a diagnosis of OAB in patients who presented to an academic urology practice, although the authors did not investigate BMI, muscle mass, or strength. 10 Specifically for BMI, many previous studies have demonstrated the importance of overweight and obesity as risk factors of OAB, 11 and our results also support these findings. Several studies have further assessed the effectiveness of bariatric surgery on OAB and have shown postoperative improvement in symptoms among obese patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this previous study, frailty was measured by TUGT and a slow TUGT exhibited a significant association with a diagnosis of OAB in patients who presented to an academic urology practice, although the authors did not investigate BMI, muscle mass, or strength. 10 Specifically for BMI, many previous studies have demonstrated the importance of overweight and obesity as risk factors of OAB, 11 and our results also support these findings. Several studies have further assessed the effectiveness of bariatric surgery on OAB and have shown postoperative improvement in symptoms among obese patients.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, body weight, muscle mass, and strength were not investigated despite being major components for determining the state of physical frailty. Both overweight/obesity and underweight were reported to be associated with OAB . In addition, body muscle mass and strength might be associated with pelvic floor muscle strength and, therefore, with bladder function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is considered a proinflammatory disease because of high accumulation of macrophages and their products within adipose tissue and other organs . In addition, this complex multifactorial metabolic problem is associated with many comorbidities, including diabetes, hypertension, heart failure, dyslipidemia, obstructive sleep apnea, weight‐related arthropathies, and urinary incontinence . Such complications very often require functional bioengineered substitutes such as artificial organs, scaffolds for tissue engineering, heart valves and other implantable devices like glucose sensors, orthopedic implants, catheters, drug‐eluting stents, or biosensors .…”
Section: Introductionmentioning
confidence: 99%
“…Un autre point important à prendre en considération est le poids ainsi que sa variation qui influent sur l'hyperactivité et les troubles urinaires (4,17,23). Pour cette raison, la majorité des études présentées étaient appariés sur le poids ou l'Indice de Masse Corporelle (IMC) et pris en compte dans l'analyse multivariée (4,(16)(17).…”
Section: Caféineunclassified